Suppression of Localized Plastic Flow in Irradiated Materials. (September 2018) - Cui, Yinan; Po, Giacomo; Ghoniem, Nasr
Abstract: Suppressing deformation localization caused by dislocation channels is crucial in the reliable service of irradiated materials. Through 3D Discrete Dislocation Dynamics simulations, the evolution of deformation localization extent is quantitatively studied, and the effect of internal dislocation structure and slip mode are revealed. Results show that to inhibit dislocation channel formation, the material is required to be pretreated so as to enhance short-range dislocation interactions. This can be attained by introducing a homogeneously dense dislocation structure before irradiation, and by loading along orientations that activate multiple slip systems. Implications for the design of radiation-resistant materials are discussed. Graphical Abstract: